Players in Mitochondrial Dynamics and Female Reproduction - Zou, Weiwei; Ji, Dongmei; Zhang, Zhiguo; Yang, Li; Cao, Yunxia (Frontiers in Molecular Biosciences, 2021)
Mitochondrial dynamics (fission and fusion) are essential physiological processes for mitochondrial metabolic function, mitochondrial redistribution, and mitochondrial quality control. Various proteins are involved in regulating mitochondrial dynamics. Aberrant expression of these proteins interferes with mitochondrial dynamics and induces a range of diseases. Multiple therapeutic approaches have been developed to treat the related diseases in recent years, but their curative effects are limited. Meanwhile, the role of mitochondrial dynamics in female reproductive function has attracted progressively more attention, including oocyte development and maturation, fertilization, and embryonic development. Here, we reviewed the significance of mitochondrial dynamics, proteins involved in mitochondrial dynamics, and disorders resulting from primary mitochondrial dynamic dysfunction. We summarized the latest therapeutic approaches of hereditary mitochondrial fusion–fission abnormalities and reviewed the recent advances in female reproductive mitochondrial dynamics.